2006
DOI: 10.1128/jcm.00980-05
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus-Specific Antibody Levels in Individuals in Argentina Who Received a One-Dose Vaccine

Abstract: In spite of active measles virus (MV) vaccination strategies, reemergence continues to occur, impairing global eradication programs. The immune status against measles was evaluated in 350 vaccinated healthy Argentine children and teenagers who received a single dose of the MV Schwarz strain Lirugen vaccine (Aventis Pasteur). Sera were assessed for immunoglobulin G (IgG) antibodies by a commercial enzyme immunoassay (EIA) (Enzygnost; Behring), an in-house EIA, and neutralization EIA. Results obtained with these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
2
11
0
1
Order By: Relevance
“…Thus, it is difficult to compare our measles IgG levels with other reports and with the conventionally accepted protective level of 200 mIU/ml [12]. However, as reported by others [13], we found that our ELISA measles IgG levels were generally correlated with the neutralizing titers (Table 1).…”
Section: Resultssupporting
confidence: 46%
“…Thus, it is difficult to compare our measles IgG levels with other reports and with the conventionally accepted protective level of 200 mIU/ml [12]. However, as reported by others [13], we found that our ELISA measles IgG levels were generally correlated with the neutralizing titers (Table 1).…”
Section: Resultssupporting
confidence: 46%
“…Interestingly in countries with high vaccination coverage and low measles incidence remarkably high rates of equivocal sera (15-25%) were noted in this age group. An increase of the portion of seronegative individuals as well as a decline of the mean antibody levels several years after measles vaccination was reported especially from countries where the measles incidence was very low, thus limiting the possibility for natural boosters (Argüelles et al, 2006;Davidkin and Valle, 1998;Miller et al, 1995;Pebody et al, 2002;Ratnam et al, 1996). After re-vaccination some seronegative individuals developed only temporarily positive antibody levels while others remained negative (Cohn et al, 1994;Matson et al, 1993;Ratnam et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent and young adults aged between 15 and 30 years were identified as a group that may require booster vaccination. Several studies showed that, by this age, the level of measles and rubella antibodies were lower than other age groups studied [11,18,22,24,26,29,30,32,36,42,84,88,91,96]. Several authors recommended that teens be re-vaccinated [24,32,36,42].…”
Section: Major Findings Of the Reviewmentioning
confidence: 99%